Critical care outcomes in resource-limited settings. Issue 5 (October 2018) - Vukoja, Marija; Riviello, Elisabeth D.; Schultz, Marcus J.
Abstract : Purpose of review: The burden of critical illness in low-income and middle-income countries (LMICs) is substantial. A better understanding of critical care outcomes is essential for improving critical care delivery in resource-limited settings. In this review, we provide an overview of recent literature reporting on critical care outcomes in LMICs. We discuss several barriers and potential solutions for a better understanding of critical care outcomes in LMICs. Recent findings: Epidemiologic studies show higher in-hospital mortality rates for critically ill patients in LMICs as compared with patients in high-income countries (HICs). Recent findings suggest that critical care interventions that are effective in HICs may not be effective and may even be harmful in LMICs. Little data on long-term and morbidity outcomes exist. Better outcomes measurement is beginning to emerge in LMICs through decision support tools that report process outcome measures, studies employing mobile health technologies with community health workers and the development of context-specific severity of illness scores. Summary: Outcomes from HICs cannot be reliably extrapolated to LMICs, so it is important to study outcomes for critically ill patients in LMICs. Specific challenges to achieving meaningful outcomes studies in LMICs include defining the critically ill population when few ICU beds exist, the resource-intensiveness of long-term follow-up, and the need for reliable severity of illness scores to interpret outcomes. Although much work remains to be done, examples of studies overcoming these challenges are beginning to emerge.